2020
DOI: 10.1101/2020.04.18.20070482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostics and prognostic potential of current biomarkers in heart failure with preserved ejection fraction: a systematic review and meta-analysis

Abstract: Aims Circulating biomarkers are commonly used in diagnosis and prognosis of heart failure with preserved ejection fraction (HFpEF) in clinical practice. However, the diagnostic and prognostic potential of current biomarkers in HFpEF remain unclear. Methods and results We conducted a search of the PubMed, Web of Science, MEDLINE and SCOPUS (1900 to January 2020) databases of all diagnostic (n=1,104) and prognostic (n=53,497) biomarkers investigated in people with HFpEF. B-type natriuretic peptide (BNP) displ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Patients with HFpEF represent nearly 50% of the HF population and is associated with a decreased life expectancy [ 26 , 28 ]. This impaired prognosis, however, is not fully explained by the associated comorbidities such as hypertension, diabetes mellitus, atrial fibrillation and obesity, as higher mortality rates have been reported in patients with HFpEF than in those with similar comorbidities but without HF [ 28 ]. Regarding NT-ProBNP, which has a high specificity but a lower sensitivity for the diagnosis of HFpEF, new biomarkers need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with HFpEF represent nearly 50% of the HF population and is associated with a decreased life expectancy [ 26 , 28 ]. This impaired prognosis, however, is not fully explained by the associated comorbidities such as hypertension, diabetes mellitus, atrial fibrillation and obesity, as higher mortality rates have been reported in patients with HFpEF than in those with similar comorbidities but without HF [ 28 ]. Regarding NT-ProBNP, which has a high specificity but a lower sensitivity for the diagnosis of HFpEF, new biomarkers need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis [ 24 ] which investigated the diagnostic potential of biomarkers in HFpEF found that the studies investigating galectin-3 as a diagnostic biomarker of HFpEF were conducted in Asia, with cut-off values of 9.55 ng/mL, 17.8 ng/mL, 20.12 ng/mL [ 28 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…N-terminal pro-BNP releases in response to chronically increased pressure in the ventricles such as in ventricular dysfunction or heart failure. Its role in heart failure is well defined [14][15][16] but its direct association in patients with mitral stenosis is not well defined in the presence of normal left ventricular function (LV). The release of BNP in patients with mitral stenosis with normal LV function is probably the result of volume and pressure overload particularly when the disease is of moderate to severe intensity that is why its significance is not well studied yet.…”
Section: Discussionmentioning
confidence: 99%